5/9/11

Test 2 Section 2 - #15 (page 456)

This is a function question, which means you're going to need to follow directions very closely. Start by understanding the definition:

x▲ = (x + 1)(x - 1)

All that means is that whatever we find to the left of the ▲, we put it through the same machinery:

x▲ = (x + 1)(x - 1)
p▲ = (p + 1)(p - 1)
[dog]▲ = ([dog] + 1)([dog] - 1)

I'm having a bit of fun with the definition, but you get the point. Let's solve this problem:

6▲ - 5▲
= (6 + 1)(6 - 1) - (5 + 1)(5 - 1)
= (7)(5) - (6)(4)
= 35 - 24
= 11

So we're looking for the answer choice that gives us the same result. Which answer choice gives you 11? Try them all to make sure, but for the sake of saving space I'm just going to do out the correct one:

3▲ + 2▲
= (3 + 1)(3 - 1) + (2 + 1)(2 - 1)
= (4)(2) + (3)(1)
= 8 + 3
= 11

Nice. That's choice (B).

No comments:

Post a Comment